Development of Gastro Retentive Drug Delivery System of Cephalexin by using Factorial Design - Prakash Rao, B.; Ashok Kottan, Neelima; Snehith, V S; Ramesh, C (Ars Pharmaceutica (Internet), 2009)
The objective of this research work was to formulate and optimize the floating drug delivery system containing cephalexin using 23 factorial design. Floating tablets were prepared by direct compression method incorporating HPMC K4M, xanthan gum, guar gum, sodium bicarbonate and tartaric acid as gas generating agent. The influence of independent variables like, polymer: polymer ratio, polymer type and tartaric acid on floating lag time and cephalexin release profile were studied. The diffusion exponent (n) of Krosmeyer Peppas for optimized formulation was found to be 0.635 which indicates the mechanism of drug release was anomalous transport. Floating lag time of optimized formulation was 1.50 min and remained buoyant for 24 hrs. Optimized formulation was checked for stability at 40ºC / 75% RH which was found to be stable. Scanning electron microscopy study revealed gel formation. FT-IR studies revealed that there was no chemical interaction between cephalexin and other excipients.